2011
DOI: 10.1111/j.1469-8137.2011.03718.x
|View full text |Cite
|
Sign up to set email alerts
|

MtbHLH1, a bHLH transcription factor involved in Medicago truncatula nodule vascular patterning and nodule to plant metabolic exchanges

Abstract: This study aimed at defining the role of a basic helix–loop–helix (bHLH) transcription factor gene from Medicago truncatula, MtbHLH1, whose expression is upregulated during the development of root nodules produced upon infection by rhizobia bacteria.We used MtbHLH1 promoter::GUS fusions and quantitative reverse-transcription polymerase chain reaction analyses to finely characterize the MtbHLH1 expression pattern. We altered MtbHLH1 function by expressing a dominantly repressed construct (CRES-T approach) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 71 publications
4
35
0
1
Order By: Relevance
“…To validate the specificity of the infected versus uninfected LCM data we looked for genes that are reported to be specifically expressed in either cell type in Medicago. Recently, a basic helix–loop–helix transcription, MtbHLH1, was shown to be expressed in Medicago nodules in the uninfected cells and vascular bundles, where it is thought to control vascular patterning and nutrient exchange [47]. In our LCM data MtbHLH1 (Mtr.10993.1.S1_at) indeed shows specific expression in the uninfected cells, confirming the reported promoter-GUS data.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To validate the specificity of the infected versus uninfected LCM data we looked for genes that are reported to be specifically expressed in either cell type in Medicago. Recently, a basic helix–loop–helix transcription, MtbHLH1, was shown to be expressed in Medicago nodules in the uninfected cells and vascular bundles, where it is thought to control vascular patterning and nutrient exchange [47]. In our LCM data MtbHLH1 (Mtr.10993.1.S1_at) indeed shows specific expression in the uninfected cells, confirming the reported promoter-GUS data.…”
Section: Resultssupporting
confidence: 89%
“…This supports a major physiological role for the uninfected cells in the export of fixed nitrogen in the form of asparagine in Medicago. Interestingly, the uninfected cell “specific” MtbHLH1 transcription factor (Mtr.10993.1.S1_at) was shown to be required for expression of the uninfected cell enriched asparagine synthase (Mtr.8499.1.S1_at), suggesting that it might bind to its promoter [47]. Furthermore, several putative amino-acid transporters, potentially involved in the transport of amino-acids to or from the infected cells, appear to be enriched in the uninfected cells of the nodule (Table S11).…”
Section: Resultsmentioning
confidence: 99%
“…Among the novel primary targets of cytokinin action identified, the NSP2 and bHLH476 TFs were linked to nodulation, suggesting their [Karas et al, 2009]; MtbHLH1 [Godiard et al, 2011]; MtbHLH658 [Zahaf et al, 2012]), previously linked to Arabidopsis cytokinin response, or related to MtbHLH476 (arrow). Complete proteins were aligned at http://www.phylogeny.fr/ using MUSCLE 3.7, PhyML 3.0 phylogenetic analysis, and TreeDyn (PHYLIP package) displays.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of genes revealed thanks to transcriptomic analyses, members of the large family of plant genes encoding small cysteine-rich proteins (NCRs) (Fedorova et al, 2002;Mergaert et al, 2003;Graham et al, 2004) were shown to play essential roles during bacteroid differentiation in indeterminate nodules but not in Lotus japonicus or soybean determinate-type nodules (Colebatch et al, 2002(Colebatch et al, , 2004Kouchi et al, 2004;Hogslund et al, 2009;Libault et al, 2010;Severin et al, 2010). Transcriptome analyses also identified TF-encoding genes upregulated in M. truncatula nodules, including MtNF-YA1 (Combier et al, 2006;Laloum et al, 2012), important for nodule meristem establishment or maintenance, MtZPT2.1 and MtEFD, involved in the differentiation of ZII and ZIII (Frugier et al, 2000;Verni e et al, 2008), and MtbHLH1, necessary for proper vascularization and metabolic exchanges between the nodule and the rest of the plant (Godiard et al, 2011).…”
Section: Introductionmentioning
confidence: 99%